The effect of role playing method on student learning outcomes in drama material - Revika Anindita Yulistia; Muhammad Zakia Firdaus; Tsalitsatul Maulidah (Journal of diversity in learning (JDIL), 2021)
This study aims to determine student learning outcomes on the understanding of drama material in Indonesian subjects. The purpose of this study was to describe and obtain information about efforts to influence the role playing method on student learning outcomes in Indonesian subjects. research procedures in this study include planning, action, observation and reflection. This study consisted of four meetings. Quantitative research methods, data collection is done through tests, observations, and documentation. The subjects of this study were students of class XI SMK Ma'arif Nu Mantup who collected 15 students, to obtain data the authors used test and non-test techniques. The results of this study indicate that the learning process using the role playing method has a significant effect on learning outcomes for students in class XI drama material. the influence of the learning process with significance on student learning outcomes pre-test results with a value of 55.07. on student learning outcomes from the post-test test with a significance value of 83.13. The student learning process has a significant effect on student learning outcomes in class XI SMK Ma'arif Nu Mantup by 30.06.